Books surreptitiously printed in England before 1640 in contemporary foreign languages - Woodfield, D; Woodfield, Denis (1964)
﻿ At least 65 of the books, pamphlets or broadsides printed in England in foreign vernaculars during the period covered by the Short Title Catalogue share a common characteristic: there is no clear indication anywhere on their title-pages, or within their colophons or texts, that they were printed in England and by English printers. Often the purpose of these ommissions was not so much to conceal the fact that the books were printed in England as to create a false impression that they were printed abroad. This thesis tries to resolve the various problems set by this class of book. As many as possible of the works have been identified, and bibliographical descriptions and photographs are given of all title-pages ornaments and capital initials contained in them. Although in the main printers have been identified through the presence of ornaments and initials to be found in other books which contain their full and clear imprint, occasionally supporting evidence of a different nature has been discovered and presented. The problems raised by these books are complex, and an Introduction of six chapters examines the background and origin of each individual item and attempts at the same time to trace the historical development of this distinctive branch of printing. Copies have been located in every major library in England and on the continent with the aim of discovering the trends and patterns of their sale and distribution, and it has been possible to distinguish sub-categories of these books which share a surprising number of characteristics. Thus in the period of nearly 90 years between the first of these publications, in 1552-3, and the delimiting date of 1640, there are three clear stages of evolution, each occupying approximately 30 years. The first, from 1553 to early 1584, is marked by the casual ommission of imprints. No fictitious imprints are found, and the motives of the various printers do not go beyond an implied intention to conceal the truth. The second stage begings in late 1584 and ends wwith the death of Sir Robert Cecil, Earl of Salisbury, in 1612. It was inaugurated by John Wolfe, a London printer who travelled and practised his craft in Italy and Germany before settin up shop in his own country. The privilege of printing certain profitable books was monopolised in late Elizabethan London by a small group of established printers, and newcomers often had difficulty in finding sufficient profitable material to keep their presses occupied. John Wolfe was one of these newcomers and in the course of his efforts to keep his presses busy he hit upon the idea of reprinting, in the original Italian, editions of well-known works by Machiavelli and Pietro Arentino which could no longer be produced in Italy after they had been placed on the recently-established Index Liborum Prohibitorum. There was no law of international copyright at that time, and in using fictitious impints in most of his early books in foreign vernaculars Wolfe was guided entirely by commercial considerations. English books printed in foriegn languages had a bad reputation in both foreign and domestic markets, since the insular English printer seldom had access to compositors with a reasonable grasp of foreign languages, and the occasional attempts to print in foreign vernaculars had usually resulted in inaccurate or even garbled texts. A statement made by John Charlewood to Giordano Bruno confirms this interpretation of Wolfe's motives; and it should be emphasised that at no time during this period did the English Government or the Stationers' Company express disapproval of the printing of any of these works. Wolfe naturally had his imitators. Charlewood in London and Joseph Barnes in Oxford both tried this expedient for increasing their sales of books in foreign vernaculars. Neither of them persevered, but the growing threat of Spanish invasion introduced a new motive for the use of fictitious imprints. The urgency of the times compelled Lord Burghley to write and get published a pamphlet called 'The Copie of a Letter ... to Don Bernadin de Mendoza'. This appeared in September, 1588, just after the news had been received of the English victory over the Spanish Armada. Its translation into Italian, specifically entered to John Wolfe, was produced with a fictitious imprint and it was the first piece of political propaganda to be surreptitiously printed in England in a foreign vernacular. Wolfe continued to produce books with misleading imprints for another three years, but in 1591 he virtually ceased to do his own printing and his place in this particular branch of the trade was taken by Richard Field. Field's first productions of this sort were his editions of the French translation of Burghley's pamphlet. These were followed by a group of books and pamphlets which are all but one characterised by bearing only the date, with occasionally a non-committal imprint such as "Nouvellement Imprimé". The exception, the Pedaços de Historia by Antonio Péres, bears the imprint: 'Impressoo in Leon'; but this was the only occasion that Field ever used a completely fictitious imprint. His later publications in this category consist of the books written by his Italian proof-reader, Petruccio Ubaldini, which appeared without any imprint at all, except for the date; and the books written, translated or edited by his Spanish proof-reader, Cipriano de Valera. The works produced by de Valera bear only Field's name translated into Spanish (Ricardo del Campo), and they have no geographical location. This imprint was designed to be misleading as most of these books were printed with the intention that some copies should be clandestinely exported to Spain. Thus during this second stage the motives of the authors and printers developed into a conscious aim of suggesting a false origin for their wares. The third stage extends from 1612 to the delimiting date, 164O. Salisbury does not seem to have been responsible for any surreptitiously printed political propaganda. After the death of his father he was by far the most powerful man in the English Government, and possibly it was because he did not use these tactics that no one else seems to have dared or cared to use them either. Three trends emerge in this final stage, and one of them may be noted in a pamphlet that was surreptitiously printed at the time of Salisbury's death. The surreptitiousness is only incidental, consisting of the omission of the imprint; and, as in the first stage, the imprint was left out rather because the edition was produced for a private order than because the printer had any intention to mislead or deceive. The second trend, concerned with the production of propaganda directed against particular groups of foreigners, was a continuation of the methods discovered by Wolfe and pioneered by Burghley. This had become a well-known and accepted strategem, and it was used on various occasions for definite purposes. The third trend, the production of illegal political propaganda directed against the home Government, was inaugurated in 1632 with Harper's edition of The Prince. It is hoped that this thesis will fill a gap in English bibliography. Books in English can be hard enough to identify when they contain authentic imprints. The problem becomes much more complicated when the books, although in English, were printed abroad with fictitious imprints, or when they were printed in England in foreign vernaculars but bore a fictitious imprint or no imprint at all. Messrs. Allison and Rogers have studied the problems of books printed abroad, and the present thesis tries to clear up some of the difficulties surrounding the books surreptitiously printed in England. Sixty-five titles are discussed, of which some two-thirds are not in STC. Appendix C provides a list of books in STC which are wrongly believed to have been printed in England; Appendix A a list of doubtful books; Appendix B a list of line-for-line foreign reprints; and Appendix J a transcript of an Armada manuscipt from the Vatican archives. Finally, in addition to describing and identifying these 65 works the thesis attempts to demonstrate the historical reasons for their appearance and to indicate the areas still to be searched and the type of book yet to be found.